Pengaruh Vitamin D Terhadap Kadar Hba1c Pada Penderita Diabetes Melitus II Di Puskesmas Rappokalling Makassar - Faradila Huath; Masriadi; Farihah Muhsanah (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
The number of diabetes cases in Makassar continues to increase year by year. From 2020 to 2021, diabetes mellitus was recorded as a chronic metabolic disease or disorder characterized by high blood sugar levels. This disease is the third most common non-communicable disease in terms of cases of 30.976 million patients. Data from the Makassar City Health Office in (2021) cases of Diabetes Mellitus will continue to increase if prevention and control are not improved. This study aims to determine the effect of sunbathing with vitamin D consumption on HbA1C levels in patients with diabetes mellitus II at the Rappokalling Health Center, Makassar. The type of research is quantitative research with an actual experiment research design (true experiment) model Pretest-Posttest With Control Group. The population of the study was all patients with Type 2 diabetes mellitus at the Rappokaling Health Center, Tammua District, Makassar City, South Sulawesi, and the research sample was 45 patients with Type 2 diabetes mellitus at the Rappokaling Health Center, Tammua District, Makassar City, South Sulawesi using the purposive sampling method. The study's results were obtained from data taken by conducting an examination, and then a data normality test was carried out. The data was analyzed using the Wilcoxon test showing that there was an effect of sunbathing on HbA1c levels in patients with diabetes mellitus II at the Rappokaling Health Center, Makassar, with a p-value of 0.000 <0.05, Sunbathing with vitamin D consumption with a p-value of 0.001 <0.05 in patients with DM II and sunbathing with vitamin D consumption with a p-value of 0.001 <0.05 in patients with DM II. This study concludes that sunbathing with vitamin D consumption affects Hba1C levels in patients with diabetes mellitus II at the Rappokalling Health Center, Makassar.